The Art of Goodbye: Medicare Covers Advance Care Planning - Lynda M. Spence (EDIS, 2018)
This 4-page document is part of a series which addresses end-of-life concerns, entitled The Art of Goodbye. The publication discusses the Patient Self-Determination Act, advance care planning, and communication about advance care planning. Written by Lynda Spence, and published by the UF/IFAS Department of Family, Youth and Community Sciences, July 2018. http://edis.ifas.ufl.edu/fy1471